The Meaning of Vlog Utilization in Enhancing Speaking Skills: A Qualitative Study of PGSD Students at Sapta Mandiri University in the Academic Year 2024/2025: Penelitian - Rika Setyawati; Alpian Husna (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study investigates the utilization of vlogs as a medium to enhance speaking skills among PGSD (Primary School Teacher Education) students at Sapta Mandiri University. Recognizing the importance of communication skills for future educators, the research aims to explore how vlogging contributes to the improvement of students' speaking abilities, confidence, and engagement in the learning process.The study employed a qualitative descriptive approach, collecting data through classroom observations, semi-structured interviews, and vlog content analysis. Thirty PGSD students participated by creating individual vlogs on topics related to education, teaching practice, and personal experiences. Data were analyzed thematically to uncover patterns and insights related to students’ experiences and perceptions.The findings revealed that vlogs served as an effective tool for self-reflection, enabling students to identify and correct speaking errors. Vlogging also significantly boosted students’ confidence, motivation, and engagement. Moreover, students viewed vlogs as a platform for creativity and authentic language practice, enhancing their ability to communicate clearly and expressively. Technical challenges were encountered, particularly in editing and uploading videos, but these also contributed to the development of students’ digital literacy skills. Peer feedback played a vital role in helping students refine their intonation, pronunciation, and delivery.In conclusion, vlogging provides a multifaceted learning experience that supports the development of speaking skills, fosters creativity, builds confidence, and promotes technological competence among PGSD students. The integration of vlogs into language instruction is recommended as an innovative and effective pedagogical strategy for enhancing communication skills in teacher education programs.